2018
DOI: 10.3390/children5030034
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Supplemental Oxygen on Obstructive Sleep Apnea of Infants

Abstract: Treatment options may be limited for infants with obstructive sleep apnea when there is no surgically correctable upper airway lesion. We therefore evaluated, retrospectively, the efficacy of low-flow oxygen as a therapeutic option for infant obstructive sleep apnea. We reviewed the medical charts of 23 infants who had undergone a therapeutic trial of low-flow oxygen during polysomnography. Split-night polysomnography was used in 21/23 subjects while 2/23 had undergone two separate, full-night polysomnography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Oxygen therapy in children at risk or with known pulmonary hypertension may be a reasonable option but yields variable reduction of the AHI. 29,40,41 The one patient in our cohort treated with oxygen had comorbid hypertension and cardiac disease, and she displayed persistent mild OSA on follow-up PSG.…”
Section: Discussionmentioning
confidence: 97%
“…Oxygen therapy in children at risk or with known pulmonary hypertension may be a reasonable option but yields variable reduction of the AHI. 29,40,41 The one patient in our cohort treated with oxygen had comorbid hypertension and cardiac disease, and she displayed persistent mild OSA on follow-up PSG.…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, an older study from 1982 reported that in a 58-year-old man with primary alveolar hypoventilation and central sleep apnea, after initiating treatment with low-flow nocturnal oxygen, there was a significant reduction in the number and duration of sleep apneas and an increase in ventilation levels during sleep 38 . Another study from 2018 by Das et al demonstrated that low-flow oxygen supplementation significantly reduced cAHI in children during both REM and non-REM sleep 39 . The underlying mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 98%
“…Supplemental oxygen, in addition to perhaps supplying a small amount of positive airway pressure, is thought to reduce the diaphragm's contracting force with the correction of hypoxemia and the related increased respiratory drive, which can contribute to airway collapse. Furthermore, treatment of hypoxemia may improve geniohyoid muscle tone (124). Supplemental oxygen therapy can be used for abolishing intermittent hypoxia in OSA.…”
Section: Other Treatmentsmentioning
confidence: 99%